Dengue fever studies in Malaysia : bulletin - 5728 Institut Penyelidikan Perubatan Malaysia; Rudnick, Albert, editor; Lim, Teong Wah, editor (Kuala Lumpur: Institute for Medical Research Malaysia, 2010)
PSZJBL